(untitled) (Global Journal of Science Frontier Research, 2015)
In Ethiopia, there are insufficient information on genetic diversity in the Ethiopian fenugreek germplasms and need to study associations among seed yield and yield related traits. The overall objective of this investigation was cluster analysis using divergence and ranging the traits which were the most contributors to variation by principal component analysis. It was undertaken on 36 geographically diverse Ethiopian germplasms of fenugreek. The germplasms were collected from different regions of the country. These germplasms were tested in a 6×6 simple lattice at South Nation and Nationality Peoples Region (NNPR), Gesha Woreda, Kefa Zone, Deka, Ethiopia in 2013 main cropping season. Distances square (D 2 ) analysis showed that 36 fenugreek germplasms grouped into six clusters. The distances were significant difference which helps for maximum genetic segregation and genetic recombination for crosses as well as obtaining heterotic response in breeding program for improving yield and yield related traits. Clustering pattern of genotypes was not related to geographical differentiation.